Content-Aware Adaptive Mechanism for Improved Digital Multimedia Delivery over Wireless channel - Ukommi, U.; Akpan, U.; Garba, S. (European Journal of Applied Sciences, 2016)
Meeting users’ satisfaction in terms of received quality of mobile media services are challenging due to dynamic channel condition and system constraints. Adaptive coding and modulation techniques improve system capacity. In this study, Content-Aware Adaptive Mechanism is investigated for improved wireless multimedia communications. The unique features of this contribution include the mechanism to exploit multimedia characteristic in the adaptation of modulation parameters for transmission of media bitstream. The aim of the study is to model an end-to-end transmission scheme capable of maximizing the limited network resources for improved mobile multimedia communications. The experimental results obtained under various test conditions demonstrate the efficiency of the proposed scheme compared to the conventional mechanism.